From PhD glut to redefined purpose: Rethinking the value and future of doctoral education - Bai, Junwen; Mujumdar, Arun S; Xiao, Hongwei (International Journal of Agricultural and Biological Engineering, 2025)
The global “PhD glut” has emerged as a critical issue with the rapid expansion of doctoral education. This oversupply has caused challenges such as intense competition for academic positions and a decline in the perceived value of doctoral degrees. To address these issues, a shift in the definition of the PhD is needed, moving towards a more versatile qualification that meets the evolving needs of society and the labor market. In the field of Agricultural and Biological Engineering (ABE), a “Solution-Driven PhD” model is proposed, integrating doctoral training with agricultural engineering enterprises and modern agricultural industry clusters. This paper explores the multifaceted challenges of the PhD glut, the need for redefining doctoral education, and the specific opportunities and strategies for transforming ABE doctoral programs to better align with global demands and future development needs. Key words: PhD glut; doctoral education; Solution-Driven PhD; Agricultural and Biological Engineering; PhD oversupply DOI: 10.25165/j.ijabe.20251802.9744 Citation: Bai J W, Mujumdar A S, Xiao H W. From PhD glut to redefined purpose: Rethinking the value and future of doctoral education. Int J Agric & Biol Eng, 2025; 18(2): 299–300.